Digitization and the Future of Natural History Collections. (7th February 2020) - Hedrick, Brandon P; Heberling, J Mason; Meineke, Emily K; Turner, Kathryn G; Grassa, Christopher J; Park, Daniel S; Kennedy, Jonathan; Clarke, Julia A; Cook, Joseph A; Blackburn, David C; Edwards, Scott V; Davis, Charles C
Abstract: Natural history collections (NHCs) are the foundation of historical baselines for assessing anthropogenic impacts on biodiversity. Along these lines, the online mobilization of specimens via digitization—the conversion of specimen data into accessible digital content—has greatly expanded the use of NHC collections across a diversity of disciplines. We broaden the current vision of digitization (Digitization 1.0)—whereby specimens are digitized within NHCs—to include new approaches that rely on digitized products rather than the physical specimen (Digitization 2.0). Digitization 2.0 builds on the data, workflows, and infrastructure produced by Digitization 1.0 to create digital-only workflows that facilitate digitization, curation, and data links, thus returning value to physical specimens by creating new layers of annotation, empowering a global community, and developing automated approaches to advance biodiversity discovery and conservation. These efforts will transform large-scale biodiversity assessments to address fundamental questions including those pertaining to critical issues of global change.